2018
DOI: 10.3390/app8040650
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of a Long-Span Concrete-Filled Steel Tube Tied Arch Bridge and the Riding Comfort of Monorail Trains

Abstract: In this study, a dynamic response analysis procedure is proposed and applied to investigate the dynamic responses of a straddle-type concrete-filled steel tube tied arch bridge under train and truck loadings. A numerical model of the coupled monorail train-bridge system is established to investigate the dynamic behaviors of the bridge under moving trains. A refined three-dimensional finite element model is built for the bridge and a 15 degrees-of-freedom vehicle model is presented for the train. The numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…In this study, differential cooling, creep, and shrinkage of bulb-tee cross sections are studied as potential reasons of crack growth. Kim and Gou et al [22][23][24][25][26][27][28][29][30] conducted experiments and comparisons between experimental results and design-equation predictions to determine the effects of steel-fiber and rebar reinforcements on the ultimate bearing strength of the local anchorage zone. The test and the comparisons between the design-equation predictions and the test results showed that the ultimate bearing strength and the section efficiency were highly affected by the reinforcement details and the concrete strength.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, differential cooling, creep, and shrinkage of bulb-tee cross sections are studied as potential reasons of crack growth. Kim and Gou et al [22][23][24][25][26][27][28][29][30] conducted experiments and comparisons between experimental results and design-equation predictions to determine the effects of steel-fiber and rebar reinforcements on the ultimate bearing strength of the local anchorage zone. The test and the comparisons between the design-equation predictions and the test results showed that the ultimate bearing strength and the section efficiency were highly affected by the reinforcement details and the concrete strength.…”
Section: Introductionmentioning
confidence: 99%
“…Pu, QH et al have studied the fatigue performance of PC beams in straddle monorail system, carried out stiffness degradation and strain change tests, tested the displacement and rotation of concrete beams and steel bars, and established a three-dimensional finite element model [14]. Gou et al have studied the dynamic characteristics of bridges under load by finite element method, and then, based on the simulation results, the influencing factors of bridges and evaluated the ride comfort of trains has been studied [15].…”
Section: Introductionmentioning
confidence: 99%
“…Model test and In-situ test have been considered as the effective approach to investigate the mechanical performance of bridge structures [8][9][10][11][12][13][14]. Reinforced concrete columns have been strengthened using different materials, such as reinforced concrete, steel, and fiber reinforced polymers Three prism specimens measuring in 150 mm × 150 mm × 300 mm were tested to determine the compressive stress-strain relationship at five days, as shown in Figure 2, in accordance with GB/T 50081-2002 [30].…”
Section: Introductionmentioning
confidence: 99%